Formamide-Based Post-impact Thermal Prebiotic Synthesis in Simulated Craters: Intermediates, Products and Mechanism - Ferus, Martin; Knížek, Antonín; Petera, Lukáš; Pastorek, Adam; Hrnčířová, Jana; Jankovič, Luboš; Ivanek, Ondřej; Šponer, Jiří; Křivková, Anna; Saeidfirozeh, Homa; Civiš, Svatopluk; Chatzitheodoridis, Elias; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Influx of matter from impacting meteoroids and hydrothermal crater weathering are important factors modifying the rock and mineral inventory of young planets undergoing heavy bombardment. These processes may have influenced not only the geochemical environment of, e.g., early Mars and other planets, but also the peculiar prebiotic chemistry on early Earth. Here, we present a synergistic experimental and computational investigation of the intermediates of chemical reactions of the formamide-based synthesis of canonical and non-canonical nucleobases by thermochemistry in hot hydrothermal crater environments. We put our findings into context with previously investigated plasma-initiated synthesis occuring directly during impact. Both processes result into the formation of all canonical nucleobases, hypoxanthine, purine, and into the onset of the simplest amino acid glycine. Furthermore, it turns out that radical species such as CN and H play a key role in the plasma-assisted impact chemistry. However, post-impact thermochemistry is essential for the origin of formamidine and 2-aminoacetonitrile, intermediate species detected in this study by means of FTIR spectroscopy.